The Painting Venatio Sacra in the Chapel of Skurbutėnai: The Influence of Poetry on the Artistic Expression of a Work of Art - Liškevičienė, Jolita (Senoji Lietuvos literatūra, 2024)
The article analyses the iconography of one Baroque painting. The canvas is kept in the Skurbutėnai chapel in the ward of Pagiriai in Vilnius district. It is listed in the Register of Movable Treasures of Lithuania and has the status of a state monument. The examination of this allegorical painting was prompted by its atypical composition, numerous Latin inscriptions, and the rare subject matter of the artwork, Venatio Sacra (‘The Sacred Hunt’). One of the starting points for this work was a line of the 30th epigram by the poet Mathias Casimirus Sarbievius (Maciej Kazimierz Sarbiewski). As it is quite a rare example in Lithuanian art, the study is focused on the influence of the poetic text on the artistic expression of a work of art and its relationship with the iconography of seventeenth-century European art, especially the genre of the emblem art, by making assumptions about the time and environment of the creation of this painting.The text concludes that this work is a painted emblem with a strongly developed visual part. Its central figure is Christ-deer running from the groups that hunt him. These groups are developed in the painting and range from individual angel youths (Genius desiderii, Genius amoris, and Genius animae Christianae) to the groups of hunters: the group of pilgrims and the heavenly host hunting with weapons and nets. The painting also incorporates a wild beast, the lion, whose appearance is attributed to the emblematic influence of the emblems of love and the image of the sneaking lion common in the Old Testament. The painting is of sacral purpose; it is intended for meditation and probably decorated the interior of a monastery or a chapel. It was probably not intended for the Skurbutėnai chapel, where it is now preserved, it, but was moved to it; it is likely to have found its way to this area through the Skurbutėnai manor. The painting is closely linked to the Jesuits as Sarbievius’ work was known and available through the Jesuit milieu. The iconography of the canvas is clearly oriented towards the Jesuit educational system or publications via books and emblematic sources available in libraries.The theme of sacred love, originally developed in the painting, was widespread in European graphic art from the early seventeenth century onwards and rapidly became popular in paintings and interior decoration in the second half of the seventeenth century. The subject of the painting echoes the theme of sacred love developed through sacred texts and images and is intended for meditation, prayer, and the cultivation of the spirit. Works of this nature were popular in monastic communities and their environment. The work is an invaluable example of local spirituality, a distinctive monument of art and writing. It is a painted emblem in which a line from Sarbievius’ epigrams, reflecting the theme of the Divine Love prevalent in European literature and art, also found an important place.
Keywords: emblem; epigram; painting; Jesuits; Skurbutėnai; Mathias Casimirus Sarbievius; Maciej Kazimerz Sarbiewski